Perbandingan indeks massa tubuh, lingkar pinggang, dan rasio pinggang pinggul sebagai faktor risiko kanker kolorektal - Khosama, Yuansun; Sapan, Heber B.; Panelewen, Jimmy; Kalesaran, Laurens T. B. (Jurnal Biomedik : JBM, 2016)
Abstract: Globally, colorectal cancer is the 4th cause of deaths. Risk factors of colorectal cancer are divided into modified and unmodified; obesity is one of the modified factors. It is accepted that insulin resistance and metabolic dysfunction act as a link between obesity and colorectal cancer. Distribution of fat tissue in Asian including Indonesian differs from that in Western people. Although of the same body mass index (BMI), Asian have higher fat tissue level than the Westerns. Body fat tissue can be measured by using BMI, waist circumference (WC), and waist-hip ratio (WHR). Acurate anthropometric measurements play some important roles in prevention of colorectal cancer. This study aimed to compare the three anthropometric parameters in colorectal cancer patients. This was a descriptive analytical study with a cross sectional design. Subjects were colorectal patients admitted to Surgery Department of Sam Ratulangi University Manado and its collaborationg hospitals from June 2015 to December 2015. There were 33 colorectal cancer patients in this study consisted of 22 males and 11 females. The ages ranged from 27 years to 77 years. The sensitivity result was as follows: BMI 33.3%, WC 51%, and WHR 42%, meanwhile the specifity result was 75.80%; 60.60%; and 60.60% respectively. The X2 test showed a P value of 0.327. Conclusion: Statistically, BMI, WC, and WHR showed no significant difference as the risk factors of colorectal cancer. However, the three parameters have to be used together to detect the accumulation of body fat tissue. It is suggested that the detection has to be applied in primary health care to diminish the colorectal cancer risk.Keywords: colorectal cancer, BMI, WC, WHRAbstrak: Kanker kolorektal (KKR) merupakan penyebab kematian keempat terbanyak di dunia. Secara garis besar faktor risiko KKR terbagi atas yang tidak dapat dimodifikasi dan yang dapat dimodifikasi, salah satunya ialah obesitas. Resistensi insulin dan disfungsi metabolik menjadi penghubung antara obesitas dan karsinoma kolorektal. Distribusi lemak tubuh pada orang Asia, termasuk Indonesia, berbeda dengan distribusi lemak tubuh pada orang Barat. Pada indeks massa tubuh (IMT) yang sama, orang Asia memiliki kadar lemak tubuh yang lebih tinggi dibandingkan orang Barat. Kadar lemak tubuh dapat dinilai melalui pengukuran IMT, lingkar pinggang (LP), dan rasio pinggang-pinggul (RPP). Penelitian ini bertujuan untuk membandingkan ketiga parameter ukuran antropometri tubuh pada pasien KKR. Penentuan patokan antropometri tubuh yang tepat membantu tindakan preventif KKR. Jenis penelitian ialah deskriptif analitik dengan desain potong lintang. Subyek penelitian ialah pasien KKR yang dirawat di Bagian Bedah Fakultas Kedokteran Universitas Sam Ratulangi Manado dan RS jejaringnya sejak bulan Juni 2015-Desember 2015. Hasil penelitian mendapatkan 33 pasien KKR (22 laki-laki dan 11 perempuan). Usia pasien berkisar 27-77 tahun. Sensitivitas IMT ialah 33,3%; LP 51%; dan RPP 42%, sedangkan spesifisitas berturut-turut ialah 75,80%; 60,60%; dan 60,60%. Uji X2 mendapatkan nilai P = 0,327. Simpulan: IMT, LP, dan RPP secara statistik tidak menunjukkan perbedaan bermakna sebagai faktor risiko KKR. Ketiganya harus diukur bersama-sama untuk mendeteksi akumulasi lemak tubuh. Disarankan deteksi harus dimulai di pelayanan primer untuk mengurangi risiko KKR.Kata kunci: KKR, IMT, LP, RPP